PELAKSANAAN LEGISLASI HAK-HAK ASASI MANUSIA DI INDONESIA - DONNI DIAN PERMADI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTFrom the analysis that has been done, it can be concluded that the juridical organic law rigorously regulates the human rights material contained in the 1945 Constitution. Such reorganization is necessary because as mandated by the 1945 Constitution that to organize those rights must first be regulated in the law (article 28 of the 1945 Constitution). And in this case the already-established law made by the government are among others: Law no. 48 of 2009 on the Principles of Judicial Power. UU no. 12 Year 2012 on National Education System. Law No.21 of 1982 on the Basic Provisions of the Press. Law No.8 of 1985 on Community Organizations. Law No.3 of 1985 on Political Parties and Work Groups. Law No.13 of 2003 on Manpower. Ministry of Manpower Decree No. KEP-150 / MEN / 2000 Concerning the Implementation Guidelines for PHK. UU no. 13 of 2006 on the Protection of Witnesses and Victims and many others.In rearranging the human rights material, the law seems to regulate it strictly, because in its arrangement there is a concept that is not clearly understood (Law No.21 of 1982). Besides, there is also a rigid formula (Law No.2 Year 1989) that can make the private sector reluctant to participate in alleviating the government's task in an effort to educate the nation. There is also a strange provision in Law no. 22 Year 1957 because workers who will perform an action must inform the employer first. Or Law No.3 and Law No.8 1985 which requires that social organizations and political parties recognize only one ideology that is Pancasila. If it refuses, the government has the right to freeze and dissolve the relevant political organization or party. Such is the re-arrangement of human rights in organic law.